Single cell RNA-seq highlights a role for a partial EMT in head and neck cancer. (4th May 2018) - Puram, Sidharth V.; Parikh, Anuraag S.; Tirosh, Itay
ABSTRACT: Studies in single cell transcriptomics have significantly expanded our understanding of tumor biology, including recent analyses in head and neck squamous cell carcinoma. Here, we focus on the role of a partial epithelial-to-mesenchymal (EMT) program in these tumors, with discussion of its dynamics, regulation, and implications for diagnostic and therapeutic approaches.